Association of Arg72Pro of P53 Polymorphism with Colorectal Cancer Susceptibility Risk in Malaysian Population - Ahmad Aizat, Abdul Aziz; Siti Nurfatimah, Mohd Shahpudin; Mohd Aminudin, Mustapha; Zaidi, Zakaria; Ahmad Shanwani, Sidek; Muhammad Radzi, Abu Hassan; Ravindran, Ankathil (Asian Pacific Organization for Cancer Prevention, 2011)
Background: Colorectal cancer (CRC) results from the interaction between environmental exposures and genetic predisposition factors. Aims: A case control study was designed and to investigate the genotype frequencies of P53Arg72Pro polymorphism in Malaysian CRC patients and healthy controls and to determine the associated risk of this polymorphism with CRC predisposition. Methods: In this case-control study, peripheral blood samples of 202 sporadic CRC patients and 201 normal controls were collected, DNA extracted and genotyped using the polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP) technique. Results: Genotype analysis showed the frequency of homozygous variant (Pro/Pro) genotype (21%) to be significantlyhigher in cases compared to controls (13%), (p=0.013). On examining the association between variant genotypes and CRC risk, the Pro/Pro homozygous variant genotype showed significantly higher risk association with CRC susceptibility (OR: 2.047, CI: 1.063-4.044, p=0.033). When stratified according to age, we observed that, individuals aged above 50 years and carriers of pro/pro genotype had significantly higher risk with OR: 3.642, CI: 1.166-11.378, p=0.026. Conclusions: Our results suggest that the codon 72 SNP which results in amino acid substitution of Arginine to Proline in cell cycle regulatory gene P53, is associated with sporadic CRC risk and carriers of Pro/Pro genotype and more than 50 years old may have high susceptibility.